Kazimov, Namiq - (:unkn) unknown (My University, 2026)
Namig Alikhan Kazimov entered the Faculty of Economics of Lomonosov Moscow State University in 1982 and graduated in 1987 with a degree in Economics, specializing as an Economist and Teacher of Political Economy. He began his professional career as a Senior Laboratory Assistant at the Department of Political Economy of the Azerbaijan Institute of Civil Engineers. From 1989 to 1996, he worked as a Lecturer. Since 1996, he has been working as a Senior Lecturer at the Department of Business Economics and Management of the Azerbaijan University of Architecture and Construction (AzUAC). Namig Alikhan Kazimov is the author of one textbook, 56 scientific articles, 48 conference papers, and 52 course curricula.